PENGARUH MODAL INTELEKTUAL DAN INTERNASIONALISASI TERHADAP ADOPSI PELAPORAN TERINTEGRASI DI INDONESIA - Arvita Kusuma; Rr. Karlina Aprilia Kusumadewi (Diponegoro Journal of Accounting, 2020)
The aim of this study is to examine the effect of intellectual capital and internationalization on the adoption of integrated reporting in Indonesia. The dependent variable in this study is adoption of integrated reporting in Indonesia. The independent variables in this study is intellectual capital, measured by the Modified Value Added Intellectual Capital Coefficient (MVAIC) proxy, and internationalization is measured by the cross-listing proxy. The population in this study are financial companies listed on the Indonesia Stock Exchange (IDX) for the period 2016-2018. The number of samples used were 195 companies using purposive sampling method. In this study there are two control variables, company size (measured by the natural logarithm of total assets) and leverage. The data processing program uses SPSS (Statistics Product and Service Solutions) version 23. The analytical method used in this study is multiple linear regression test. The results showed that intellectual capital had a significant influence on the adoption of integrated reporting. Meanwhile internationalization had no significant influence on the adoption of integrated reporting.